2012
DOI: 10.1001/archgenpsychiatry.2011.135
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Multifamily Groups to Improve Treatment Adherence in Mexican Americans With Schizophrenia

Abstract: Multifamily group therapy specifically tailored to improve medication adherence through a focus on the beliefs and attitudes of the target population is associated with improved outcome for Mexican American adults with schizophrenia-spectrum disorders. Trial Registration  clinicaltrials.gov Identifier: NCT01125267.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 43 publications
1
80
1
1
Order By: Relevance
“…Cultural schemas or scripts associate illness representations with specific types of self-coping and help seeking, including the perceived relevance and efficacy of mental health treatments (Al-Krenawi et al, 2009; Kung & Lu, 2008; Saint-Arnault & Shimabukuro, 2012). Cultural adaptations of treatment interventions incorporating cultural scripts may enhance patient engagement and outcomes (Griner & Smith, 2006; Kopelowicz et al, 2012), indicating the value of identifying cultural models and interpretations before treatment (Lewis-Fernández et al, 2013). Non-medical forms of self-coping and help seeking are common and merit clinical attention because they may complement or conflict with psychiatric care (Bhikha, Farooq, Chaudhry, & Husain, 2012; Brown et al, 2011; Zafar et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Cultural schemas or scripts associate illness representations with specific types of self-coping and help seeking, including the perceived relevance and efficacy of mental health treatments (Al-Krenawi et al, 2009; Kung & Lu, 2008; Saint-Arnault & Shimabukuro, 2012). Cultural adaptations of treatment interventions incorporating cultural scripts may enhance patient engagement and outcomes (Griner & Smith, 2006; Kopelowicz et al, 2012), indicating the value of identifying cultural models and interpretations before treatment (Lewis-Fernández et al, 2013). Non-medical forms of self-coping and help seeking are common and merit clinical attention because they may complement or conflict with psychiatric care (Bhikha, Farooq, Chaudhry, & Husain, 2012; Brown et al, 2011; Zafar et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, intervention content should be tailored to the individual rather than across a cultural group. Kopelowicz et al [62 ▪▪ ] reported a culturally adapted family intervention for Mexican American patients with schizophrenia, which improved adherence at 12 months postintervention, illustrating ways in which the intervention content and delivery can be addressed to barriers specific to the patient group without relying on generalizations about which barriers patients would face on the basis of their background. For example, they tailored intervention content on the basis of the outcomes from individual interviews with patients.…”
Section: New Developments In Adherence Interventionsmentioning
confidence: 99%
“…Professional support to such families may alter their situation, reduce their burden and increase their sense of security (Bademli & Cetinkaya Duman, 2014;Chien & Norman, 2009;Kopelowicz et al, 2012;Rummel-Kluge, Pitschel-Walz, Bäuml, & Kissling, 2006).…”
Section: Introductionmentioning
confidence: 99%